Hypomagnesaemic tetany. Issue 4 (April 1996) - Ramage, I J; Ray, M; Paton, R D; Logan, R W; Beattie, T J
Abstract : Hypomagnesaemic tetany (hypomagnesaemic tetany with secondary hypocalcaemia) is a rare inherited form of hypomagnesaemia. Initial reports involved affected males only; however, affected females have also been reported. The case of a child with hypomagnesaemic tetany is described, the biochemical and genetic aspects of this condition are reviewed and the importance of the assessment of renal magnesium excretion in patients presenting with hypomagnesaemia is highlighted.